Simulation of Temperature and Estimation of Tool Wear in Cryogenic Assisted Electrical Discharge Machining Process Using Finite Element Approach - Sharma, Jashan (My University, 2016)
EDM is a process that is based on removing material from a conducting workpiece by means of a series of repeated electrical discharges between tool electrode (cathode) and the workpiece (anode) in the presence of a dielectric fluid. Despite all the advantages, the EDM process is not free from drawbacks. One of the major drawbacks is the high rate of electrode wear. Cryogenic assisted EDM is a hybrid process which utilizes the cooling properties of liquid nitrogen to reduce the temperature of the electrode so as to reduce electrode wear. Experimentally it has been proved that cryogenic cooling in EDM has reduced tool wear. However there exist no information regarding the size and dimensions of the crater formed in cryogenic assisted EDM process. Further the effect of cooling on temperature is also not available. Therefore in this present work, an effort has been made to study the effect of cryogenic cooling on temperature and the estimation of the size and dimensions of the crater on tool in cryogenic assisted EDM process. Temperature simulations have been performed for both conventional EDM process and cryogenic assisted EDM process to understand the temperature distribution along the length and diametrical axis of the tool electrode. The finite element approach has been employed to predict the temperature profile on the tool electrode under various operating conditions. Further in the work, an estimation of the radius and depth of crater has been performed in order to predict the tool electrode wear rate for both conventional EDM and cryogenic assisted EDM. An algorithm has been developed that reads and plots the temperature distribution along x and z axis of the surface of the tool giving radius and depth of crater. Further, using the radius and depth of crater, volume of melted portion of tool electrode and electrode wear rate for both conventional EDM and cryogenic assisted EDM have been calculated. It has been observed that cryogenic assisted EDM has lower tool temperature as compared to conventional EDM process. It has also been observed that the radius and depth of crater is smaller in cryogenic assisted EDM as compared to conventional EDM. Further it has been established that the tool electrode wear is more in conventional EDM process as compared to cryogenic assisted EDM process.
Keywords: Conventional EDM; Cryogenic assisted EDM; Electrode wear rate; Temperature distribution; Radius of crater; Depth of crater